Analisis Kepatuhan Lembaga Keuangan Syariah terhadap Fatwa DSN-MUI tentang Investasi Emas di Indonesia - Putri Nabila, Cantika; Sukamto; Aslikhah (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the level of compliance of Islamic financial institutions (IFIs) in Indonesia with the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Fatwa No. 77/DSN-MUI/VI/2010 concerning gold investment. The fatwa serves as an essential guideline to ensure that gold investment practices, both physical and digital, adhere to Sharia principles, particularly regarding ownership and contractual transactions. This research employs a qualitative approach using a descriptive method through a literature review of the DSN-MUI fatwa, Financial Services Authority (OJK) regulations, and gold investment practices in several Islamic financial institutions. The findings indicate that most IFIs have complied with the fatwa, especially in implementing murabahah contracts and ensuring real ownership of gold assets. However, challenges remain in the implementation of digital gold investment, which requires stricter supervision and improved public literacy. This study highlights the importance of synergy between DSN-MUI, OJK, and Islamic finance industry players in strengthening Sharia-compliant governance in gold investment practices.